Applied clinical and pathogenetic aspects of interdisciplinary cooperation in the diagnosis and treatment of concussion of brain - V. N. Hertsev; A. N. Stoyanov; T. I. Bocherova (Kazimierz Wielki University, 2017)
The article discusses the issues of pathogenesis and diagnostics of different variants of dizziness, as one of the main symptoms of traumatic brain injury. Along with traumatic brain injury raises concussion of the labyrinth benign paroxysmal positional vertigo and others described a range of diagnostic assessment techniques and differential diagnosis of post-traumatic nystagmus, as well as the adequacy of the practical application of a number of vestibulometric studies, caloric tests, tests, medical maneuvers, and their effectiveness from a position of evidence-based medicine.